1 - L’Amérique du Sud ou l’émergence d’un nouveau théâtre des migrations africaines - Minvielle, Régis (Africa Development, 2021)
The migration of Africans to Latin American countries has become a new trend in the migration pattern of Africans. From the 1990s, and especially since the 2000s, migrants, mainly from West Africa, have found a new migratory route in which Brazil and Argentina are the preferred destinations. These new routes are being explored not just as a response to the stern immigration policies of countries in the North but also because of the economic opportunities, favourable conditions and histories of groups and individuals. While the vast majority engage in street trading, driven in particular by the Senegalese Mourid community, others seek to make their mark in football and business.